A Method for Extending the Bandwidth of Metamaterial Absorber - Hong-Min Lee; Hyung-Sup Lee (International Journal of Antennas and Propagation)
We present a method for extending the bandwidth of a metamaterial absorber (MMA) with multiresonance structure. The basic unit cell of the MMAs consists of a periodic arrangement of an electric-LC (ELC) resonator and a square loop structure. The absorption bandwidth of an MMA is effectively extended by combining five unit cell structures with different geometric dimensions into a coplanar unit cell. Experimental results show that the fabricated MMA is 0.8 mm (0.0026 λ0) thick with a peak absorption rate of 93% at 10 GHz and a full width at half maximum (FWHM) bandwidth of 970 MHz.